DEMOGRAPHIC PROFILE AND CLINICAL OUTCOMES OF ALUMINUM PHOSPHIDE POISONING: A PROSPECTIVE STUDY - HUSSAIN, SAJJAD; SAROJ, SHWETA; PAL, V. (International Journal of Current Pharmaceutical Research, 2025)
Objective: To analyze the demographic distribution, clinical presentation, and outcomes of ALP poisoning cases admitted to a tertiary care hospital in Bhopal, Madhya Pradesh. Methods: A prospective observational study was conducted on 44 patients diagnosed with ALP poisoning over a one-year period. Data were collected on age, gender, domicile, clinical symptoms, and outcomes. Results: The majority of cases occurred in the 21–30 age group (56.82%), with males (56.82%) slightly more affected than females (43.18%). Rural and urban populations were equally affected (50% each). Common symptoms included nausea (38.64%), vomiting (34.09%), and diarrhea (22.73%). Mortality was high, with (72.73%) of patients succumbing to the poisoning. Conclusion: ALP poisoning continues to be a serious public health issue in both rural and urban India. The high fatality rate underscores the need for tighter control on its sale and improved clinical management strategies.